Identifying suitable icon button for museum application interface using online card sorting method - Mohammad Shuhaili, F. (Springer, 2019)
A good interface is made up of components that allow users to readily comprehend the conceptual model and know what interacting on an interface is like. There are many graphical components in an interface to help user interacts which include icon buttons. The countless number and range of icon buttons comes with a need to define the most appropriate set for the interface of museum implementation. This paper presents a card sorting method that uses feedback from users to obtain an efficient classification of possible navigation structure icon buttons. It interprets the exploratory analysis of a histogram matrix related to the final categories of cards used in the study. It focuses on the details of making a decision about the final categories and associated labels. It also helps in making an informed judgment when multiple interpretations of data are possible. The study findings suggest that âplay, pause and stopâ, âspeakerâ, and âvideoâ, the icon representation on the buttons could be a set of potential signifier for a museum interface. Â© Springer Nature Switzerland AG 2019.